Alterations in regional homogeneity assessed by fMRI in patients with migraine without aura stratified by disease duration - Zhao, Ling (Springer, 2013)
BACKGROUND: Advanced neuroimaging approaches have been employed to prove that migraine was a central nervous system disorder. This study aims to examine resting-state abnormalities in migraine without aura (MWoA) patients stratified by disease duration, and to explore the neuroimaging markers for reflecting the disease duration. METHODS: 40 eligible MWoA patients and 20 matched healthy volunteers were included in the study. Regional homogeneity (ReHo) analysis was used to identify the local features of spontaneous brain activity in MWoA patients stratified by disease duration, and analysis was performed to investigate the correlation of overlapped brain dysfunction in MWoA patients with different disease duration (long-term and short-term) and course of disease. RESULTS: Compared with healthy controls, MWoA patients with long-term disease duration showed comprehensive neuronal dysfunction than patients with short-term disease duration. In addition, increased average ReHo values in the thalamus, brain stem, and temporal pole showed significantly positive correlations with the disease duration. On the contrary, ReHo values were negatively correlated with the duration of disease in the anterior cingulate cortex, insula, posterior cingulate cortex and superior occipital gyrus. CONCLUSIONS: Our findings of progressive brain damage in relation to increasing disease duration suggest that migraine without aura is a progressive central nervous disease, and the length of the disease duration was one of the key reasons to cause brain dysfunction in MwoA patients. The repeated migraine attacks over time result in resting-state abnormalities of selective brain regions belonging to the pain processing and cognition. We predict that these brain regions are sensitive neuroimaging markers for reflecting the disease duration of migraine patients without aura.